The Effect of w/c Ratio of Compacted Bored Pile to Friction Resistance of Unjani Clay - Agus Sulaeman; Muhamad Agung; Regi Fasya Septrian (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2021)
The small scale physical model of drum type was set-up to obtain the effect of water cement ratio (w/c) to pile capacity and original soil. The simulation of the process of providing bored piles model, soils model, installation and tests (pile loading tests and direct shear tests) under different water cement ratio of mortar and various moisture content of clay were done. The results reveal that the higher water content of original clay the bigger friction resistance, Î± value as clay soil is softer and the optimum w/c-ratio (w/c = 0,4) provides more pile capacity. It is understandable that water plays an important role, contributes to the change of surrounding clay properties. The improvement of Su ( % increase) due to compaction of concrete in bored pile, migration of moisture and reaction with surrounding clay leads to take benefit of design and construction of bored pile in clay soil for the sake of efficiency and stability.